Amplifying voices, shaping culture: A critical examination of social media’s influence on socio-cultural issues in Nigeria - Adams, Emmanual Jibb (Yayasan Mitra Persada Nusantara, 2024)
This study explores the impact of social media on promoting socio-cultural issues in Nigeria. Using a qualitative research approach, the study analyzes the role of social media in amplifying cultural trends, preserving and promoting cultural heritage, facilitating global engagement with Nigerian cultural events, and promoting positive socio-cultural change. The study also identifies challenges such as the spread of misinformation, cyberbullying, data privacy concerns, and the digital divide. Theoretical frameworks such as Agenda Setting Theory and Cultural Diffusion Theory are employed to comprehensively explore how social media influences and diffuses socio-cultural issues in Nigeria. The study recommends promoting digital literacy, encouraging responsible social media use, strengthening regulatory frameworks governing social media platforms, addressing the digital divide, and fostering collaborative efforts between government, civil society, and social media companies to effectively address these challenges and harness the transformative potential of social media for positive socio-cultural change in Nigeria.